2015
DOI: 10.5173/ceju.2015.571
|View full text |Cite
|
Sign up to set email alerts
|

Extrarenal nephroblastoma

Abstract: IntroductionNephroblastoma is one of the most common solid tumours in children. The occurrence of extrarenal nephroblastoma is exceedingly rare. What can be defined as extrarenal Wilms’ tumor must satisfy the following criteria: histologically confirmed nephroblastoma and extrarenal location.Material and methodsCurrent data on extrarenal nephroblastoma based on a selective review of the literature.ResultsThe retroperineal location is reported to be typical in males, whereas the inguinal region is believed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Nephroblastoma is one of the most common solid tumours in children, with an annual incidence rate of 1 case per 100,000 children. This disease comprises 8–10% of all neoplasms in that group [1, 2]. The peak incidence occurs in children, between 1 to 5 years of age [1, 2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nephroblastoma is one of the most common solid tumours in children, with an annual incidence rate of 1 case per 100,000 children. This disease comprises 8–10% of all neoplasms in that group [1, 2]. The peak incidence occurs in children, between 1 to 5 years of age [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…This disease comprises 8–10% of all neoplasms in that group [1, 2]. The peak incidence occurs in children, between 1 to 5 years of age [1, 2]. Although the pathogenesis of nephroblastoma remains undiscovered, increasing evidence has suggested that multiple signalling pathways, such as microRNAs, and epigenetic mechanisms play pivotal roles in its progression.…”
Section: Introductionmentioning
confidence: 99%
“…Nephroblastoma, also called Wilms' tumor, is one of the most common solid tumors in children, with an annual incidence rate of 1 case per 100,000 children [11]. It is a prototypical embryonal malignancy of young children and infants [12].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is given to those patients in whom the tumor is unresectable or have gross residual disease, recurrence or metastasis. [3][4][5] The overall survival outcome at 2 years in the reported ERWT cases is approximately 85% and mortality rate 5%, which is equal to that of renal WT. We present a successfully treated case of ERWT occurring in urinary bladder, coupled with review of relevant literature.…”
Section: Introductionmentioning
confidence: 92%